The Acculturation Strategy of the Tabut Community in Bengkulu - Nelly Marhayati; Suryanto Suryanto (Studia Islamika, 2017)
This research examines the acculturation strategy of the Tabut community, a minority group in Bengkulu. Acculturation occurs when two or more cultures meet, and the purpose of an acculturation of an acculturation strategy is to harmonize the contact. According to the Berry perspective, there are four strategies that groups or individuals can apply during acculturation. These are: integration, separation, assimilation, and marginalization. Most cultures in Indonesia, physical or non-physical, have been formed through an acculturation process. The Tabut tradition in Bengkulu is an example of a non-physical cultural process of acculturation. The Tabut came to Bengkulu from Punjab hundreds of years ago, and the long process of acculturation has occurred within the community and through their traditions. An integration strategy has been used by the Tabut community to preserve their heredity. In this context integration means maintaining the original culture and perceived cultural contact.DOI: 10.15408/sdi.v24i3.4319